Reasons for discordance between antiretroviral adherence measures in adolescents. Issue 9 (2nd September 2022) - Lowenthal, Elizabeth D.; Ohrenshall, Rachel; Moshashane, Neo; Bula, Boineelo; Chapman, Jennifer; Marukutira, Tafireyi; Tshume, Ontibile; Gross, Robert; Mphele, Seipone
ABSTRACT: Adolescents with suboptimal medication taking may deceive caregivers about non-adherence. We conducted a 5-year longitudinal study of adolescents monitored simultaneously with both easily manipulated (e.g., self-report) and hard to manipulate (e.g., microelectronic data) strategies. Adolescents with repeatedly high adherence on the former and low adherence on the latter were invited along with their parental figures ("parents") to participate. We conducted focus groups and semi-structured interviews, separately for adolescents and parents, to elucidate drivers of discordant measures. Forty-seven adolescents and 26 parents participated in focus groups and 4 adolescents were interviewed. Adolescents described hiding pills, discarding pills, and lying. Their motivations included fear of disappointing those who care about them, desire to avoid admonishment by parents and clinic staff, and desire to avoid remedial adherence counseling. Both adolescents and parents considered negative feedback for prior poor adherence to be key motivation to hide current poor adherence from clinic staff. Providing positive feedback for truth-telling, rather than for "evidence" of excellent adherence, might help adolescent patients and their parents to develop stronger treatment alliances with each other and with clinic staff. Such alliances would allow adherence interventions to be better targeted and more fruitful in increasing adherence.